The Self Care Agency pada Pasien Diabetes Mellitus Tipe II di Puskesmas Payung Sekaki Kota Pekanbaru - Wiwik Norlita; Isnaniar; Aufa Denof Utari (As-Shiha: Jurnal Kesehatan, 2025)
Diabetes Mellitus is a non-communicable disease (NCD) which is a global health problem and is often not realized by sufferers in the early stages. Diabetes Mellitus occurs due to disturbances in the balance of blood sugar levels, impaired insulin function, abnormalities in pancreatic function in insulin secretion, and concentrated increases in blood sugar levels in the liver with the second highest prevalence globally after hypertension. Objective: This study aims to find out about "How Self Care Agency Appears in Type II Diabetes Mellitus Patients" at the Payung Sekaki Community Health Center, Pekanbaru City. Time: This research was conducted at the Umbrella Sekaki Community Health Center, Pekanbaru City, which was carried out on 12-21 June 2024. Method: The type of research used was quantitative with a descriptive type of research, namely providing a description of self-care behavior (self-care agency) in patients with type 2 diabetes mellitus. Data was collected using a questionnaire and conducting interviews with 40 DM patients at the Umbrella Sekaki Community Health Center, Pekanbaru City. Accidental sampling technique. Results: The results of this research from 40 respondents who carried out Self Care Agency were 23 respondents (57.5%). Conclusion: The most self-care agency description of the 40 respondents was poor with 25 respondents (62.5%), followed by moderate with 11 respondents (27.5%), and finally good with 4 respondents (10.0%).